MeaA, a Putative Coenzyme B(12)-Dependent Mutase, Provides Methylmalonyl Coenzyme A for Monensin Biosynthesis in Streptomyces cinnamonensis - Zhang, Weiwen (American Society for Microbiology, 2001)
The ratio of the major monensin analogs produced by Streptomyces cinnamonensis is dependent upon the relative levels of the biosynthetic precursors methylmalonyl-coenzyme A (CoA) (monensin A and monensin B) and ethylmalonyl-CoA (monensin A). The meaA gene of this organism was cloned and sequenced and was shown to encode a putative 74-kDa protein with significant amino acid sequence identity to methylmalonyl-CoA mutase (MCM) (40%) and isobutyryl-CoA mutase (ICM) large subunit (36%) and small subunit (52%) from the same organism. The predicted C terminus of MeaA contains structural features highly conserved in all coenzyme B(12)-dependent mutases. Plasmid-based expression of meaA from the ermE∗ promoter in the S. cinnamonensis C730.1 strain resulted in a decreased ratio of monensin A to monensin B, from 1:1 to 1:3. Conversely, this ratio increased to 4:1 in a meaA mutant, S. cinnamonensis WM2 (generated from the C730.1 strain by insertional inactivation of meaA by using the erythromycin resistance gene). In both of these experiments, the overall monensin titers were not significantly affected. Monensin titers, however, did decrease over 90% in an S. cinnamonensis WD2 strain (an icm meaA mutant). Monensin titers in the WD2 strain were restored to at least wild-type levels by plasmid-based expression of the meaA gene or the Amycolatopsis mediterranei mutAB genes (encoding MCM). In contrast, growth of the WD2 strain in the presence of 0.8 M valine led only to a partial restoration (<25%) of monensin titers. These results demonstrate that the meaA gene product is significantly involved in methylmalonyl-CoA production in S. cinnamonensis and that under the tested conditions the presence of both MeaA and ICM is crucial for monensin production in the WD2 strain. These results also indicate that valine degradation, implicated in providing methylmalonyl-CoA precursors for many polyketide biosynthetic processes, does not do so to a significant degree for monensin biosynthesis in the WD2 mutant.